Estimation and Characterization of Dengue Serotypes in Patients Presenting with Dengue Fever at Makkah Hospitals - Sami Melebari; Abdul Hafiz; Hatim A. Natto; Mohamed Osman Elamin; Naif A. Jalal; Ashwaq Hakim; Safiah Rushan; Othman Fallatah; Kamal Alzabeedi; Feras Malibari; Hutaf Mashat; Aisha Alsaadi; et al. (Tropical Medicine and Infectious Disease)
Dengue fever is caused by four common serotypes of the dengue virus (DENV-1, DENV-2, DENV-3, and DENV-4). Patients infected with one serotype may develop lifelong serotype-specific protective immunity. However, they remain susceptible to reinfection with the other serotypes, often increasing the risk of severe forms of dengue. This cross-sectional study investigates the prevalence of the four dengue serotypes in patients who presented with dengue fever at Makkah hospitals between April 2023 and May 2024. Data were collected from the medical records of the Regional Laboratory in Makkah, Saudi Arabia. The 238 positive dengue samples included 185 samples (77.73%) from male patients. The average age of the patients was 37.65 years (SD = 15.05). Dengue type 2 was the most common serotype, followed by type 1, type 3, and type 4. Most of the dengue patients were Saudi nationals, followed by Egyptians. There were 11 dengue-positive samples that were not diagnosed with any of the four dengue serotypes. Since Makkah receives numerous international travelers, these samples might contain novel dengue serotypes circulating in different parts of the world. This study underscores the need for the continuous monitoring of dengue serotypes to predict potential outbreaks and mitigate the risk of severe dengue in susceptible populations.